2010
DOI: 10.1158/1940-6207.capr-09-0260
|View full text |Cite
|
Sign up to set email alerts
|

Berries and Ellagic Acid Prevent Estrogen-Induced Mammary Tumorigenesis by Modulating Enzymes of Estrogen Metabolism

Abstract: To determine whether dietary berries and ellagic acid prevent 17β-estradiol (E 2 )-induced mammary tumors by altering estrogen metabolism, we randomized August-Copenhagen Irish rats (n = 6 per group) into five groups: sham implant + control diet, E 2 implant + control diet (E 2 -CD), E 2 + 2.5% black raspberry (E 2 -BRB), E 2 + 2.5% blueberry (E 2 -BB), and E 2 + 400 ppm ellagic acid (E 2 -EA). Animals were euthanized at early (6 wk), intermediate (18 wk), and late (24 wk) phases of E 2 carcinogenesis, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 51 publications
2
81
2
1
Order By: Relevance
“…This study also demonstrated that the anthocyanin fraction of black raspberries (BRB) was as effective in preventing chemically-induced esophageal tumors in rats as whole BRB powder [6]. Our own studies have shown significant inhibition of breast cancer in the rat model by both blueberry (BB) and BRB, indicating that berries are chemopreventive beyond the GI tract [7][8][9]. Our studies with BB diet have also shown that berry anthocyanidins are bioavailable beyond the GI as we could detect all anthocyanidins in lung tissues [10].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This study also demonstrated that the anthocyanin fraction of black raspberries (BRB) was as effective in preventing chemically-induced esophageal tumors in rats as whole BRB powder [6]. Our own studies have shown significant inhibition of breast cancer in the rat model by both blueberry (BB) and BRB, indicating that berries are chemopreventive beyond the GI tract [7][8][9]. Our studies with BB diet have also shown that berry anthocyanidins are bioavailable beyond the GI as we could detect all anthocyanidins in lung tissues [10].…”
Section: Introductionmentioning
confidence: 75%
“…For the preparations of the BB and BRB diet, AIN 93M diet was powdered and mixed with BB and BRB powder at 5% and 2.5% (w/w), respectively, and stored at 4 • C until use. The diets were isocaloric and the recipe used was the same as described by us elsewhere [8,16,17].…”
Section: Dietmentioning
confidence: 99%
“…Anthocyanins are abundant flavonoid constituents existing in colorful fruits and vegetables. It is reported that anthocyanins enriched foods can inhibit the development of cancer in carcinogen treated animals and in animals with a hereditary predisposition to cancer (Aiyer et al, 2010;Stoner et al, 2010).As shown in this study, the effective dose was much higher than normal chemical clinic medication mainly due to the low abundance of active ingredients in BRACs, poor absorption and rapid degradation of anthocyanins in gastrointestinal tract (Dreiseitel et al, 2009;Forester et al, 2010).…”
Section: Discussionmentioning
confidence: 56%
“…26 It was revealed by another study that supplementation of HER2/neu-overexpressing transgenic mice with resveratrol delayed spontaneous mammary tumor development and reduced metastasizing capacity by downregulating the expression of HER2/ neu and induction of apoptosis in tumor cells. 42 Ellagic acid present in berries was reported to significantly reduce the breast cancer burden on rats according to a study conducted in 2010 by Aiyer et al 43 The induction of breast cancer was associated with increase in a number of metabolic enzymes including cytochrome P450, 17β-HSD, and catechol-O-methyltransferase. The flavonoid quercetin has been reported to show apoptotic activities in breast tumors in vivo.…”
Section: In Vivo Studiesmentioning
confidence: 99%